2016
DOI: 10.1017/s0212610916000136
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Impact of Sovereign Defaults in Latin America 1870-2012

Abstract: This article analyzes sovereign debt defaults in four Latin American countries—Argentina, Brazil, Chile and Mexico—for the period 1870-2012. The impact of sovereign defaults on real GDP growth is generally short-lived, while the impact in terms of output losses is deep and lasts long. Defaults in the period 1972-2012 show a deep and long-lasting impact compared to defaults in earlier periods. Moreover, the length of the contraction that follows a default is associated with favourable international conditions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Later, Cerra and Saxena (2008) showed that devaluations associated with debt crises were especially harmful in the short run in Latin America. In fact, devaluations are typically associated with rising debt costs (Bordo and Rockoff 1996) and, ultimately, sovereign debt default (Boonman 2017). Kohn et al (2020), however, described how the increase in exports stimulates aggregate demand following large devaluations, thanks to firms' sales reallocation across markets.…”
Section: Literature Review and Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Cerra and Saxena (2008) showed that devaluations associated with debt crises were especially harmful in the short run in Latin America. In fact, devaluations are typically associated with rising debt costs (Bordo and Rockoff 1996) and, ultimately, sovereign debt default (Boonman 2017). Kohn et al (2020), however, described how the increase in exports stimulates aggregate demand following large devaluations, thanks to firms' sales reallocation across markets.…”
Section: Literature Review and Contributionmentioning
confidence: 99%
“…Later, Cerra and Saxena (2008) showed that devaluations associated with debt crises were especially harmful in the short run in Latin America. In fact, devaluations are typically associated with rising debt costs (Bordo and Rockoff 1996) and, ultimately, sovereign debt default (Boonman 2017). Kohn et al .…”
Section: Literature Review and Contributionmentioning
confidence: 99%